Analysis of Travellers' Satisfaction on Transport Chains - Cees Gorter; Peter Nijkamp; Rob Vork (Tinbergen Institute, 1999)
This paper focuses on the network character of a multimodal transportsystem in which interconnectivity is the key determinant of itsperformance, relative to unimodal transport opportunities. Theemphasis is on the viability of chain mobility in public transport byanalyzing the satisfaction of travellers on a transferpoint withrespect to its accessibility, the parking facilities offered and theschedule coordination in the central node. The statistical analysis,based on individual, subjective responses on the performance of twoDutch railway stations, enables to identify the degree ofsatisfaction of various groups of travellers in regard to theperformance of a multimodal network. This finding may prove to beuseful for network operators who aim at a complementarity orcooperation with unimodal transport systems.
Keywords: 330; Verkehrsinfrastruktur; Verkehrsteilung; Beziehungsmarketing; Niederlande